Effects of nano copper used in seed treatment for germination, growth, and productivity of maize - Hien, Le Thi; Van, Nguyen Tuong (Academia Journal of Biology, 2018)
Recently, metal and other nanoparticles have been widely used to improve crop growth and development, reduce used chemical amount, increase safety of agricultural products and prevent soil and water pollution. Seed treatment technology with metal nanoparticles to stimulate seed germination and improve crop yields has been reported in several studies. In order to assess the safety of the use of metal nanoparticles in agriculture production, in this study the effect and safety of seed treatment with nanoparticles (nCu) prior to sowing on the germination, growth, development, productivity and quality of maize (Zea mays L.) were evaluated in the field conditions. Seeds of maize cultivar LVN 092 were treated with nCu at different concentrations before planting. Germination and plant growth rates, plants yield and grain nutrition were monitored and evaluated. The obtained results showed that treatment of maize seed with nCu at a concentration of 20 mg/kg seed increased germination after 7 days of sowing as well as the theoretical and actual yields compared to the control and the treatment of 1000 mg nCu/1 kg seeds. Other agricultural characteristics, such as the development rate, plant height, grain nutritional content including moisture, ash, total fiber, crude protein, minerals were not significantly between treatments and the control. Therefore, the seed treatments with metal nanoparticles can be contribute to improve agriculture production without impact to quality of crops.